Some Problems in the Preparation of a Paper to be Published in the Context of Evidence-Based Medicine - I. O. Zaks; A. M. Golubev; Yu. A. Gryzunov (Общая реаниматология)
To process a material and to prepare it to be published is a most topical problem in the context of evidence-based medicine. The paper lays down basic requirements for paper in this context. It considers all the constituents: abstract, introduction, materials and methods, results and their discussion, references. Particular emphasis is laid on the description of methods of biomedical studies.